Vigilance home security system (VHS System) - Noorshafiza, Muhaidi (2011)
Home security system is needed for occupants' convenience and safety.The purpose of this project is to presents a prototype of a Vigilance Home Security System (VHS System). The objective of this project is to provide the prototype of low cost home security system which home owner do not need to pay for monthly fee for company that offers Central Monitoring Service (CMS) for home security. Fully-monitored system is by far the most effective home security solution.The problems come when the users need to spent a lot of money for setup, equipment, monthly monitoring fees, and even warranties. These types of home security system not afford to have by low income home owner. Furthermore,the objective is to develop a prototype of silent home security system,it did not create a loud blast sound which is noticeable to the intruder(s)or create disturbance to the neighborhood, instead it notify the user or homeowner through the text message of a GSM system. In a remote area, high blast sound of alarm system would not create attention from people all around.VHS system is an ideal solution for smaller home,apartment and condominium. Small business office, small factories or home often neglect the security requirement.